Two Inuit families in snow house, Cape Fullerton, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
A group of five Inuit identified as two Inuit families sit inside a snow house at Cape Fullerton, Hudson Bay, April 10, 1901. One of the group is a young child. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo #44, #70. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Comer identified this group as two families of the "Show-noc-tock tribe who have come to trade traveling more than 200 miles to get here." Designation of group is uncertain, but they probably came from the Baker Lake area.